Heat Reflective Thin-Film Polymer Insulation with Polymer Nanospheres—Determination of Thermal Conductivity Coefficient - Danuta Król; Przemysław Motyl; Joanna Piotrowska-Woroniak; Mirosław Patej; Sławomir Poskrobko (Energies, 2022)
In this paper, a method to determine the thermal conductivity coefficient λ in a 200 μm thick heat reflective paint layer, filled with polymer nanospheres with a Total Solar Reflectance (TSR) of 86.95%, is proposed and presented. For this purpose, a “hot box”-type (cube-shaped) test rig was built to carry out experimental tests to measure the temperature distribution on the surface of a double-layer wall containing the material under investigation. Together with the experimental studies, a CFD numerical model was prepared to understand the nature of flow and heat transfer inside the cube—the test chamber. Based on the proposed measurement and analysis method, the thermal conductivity coefficient of the heat reflective coating layer was λ = 0.0007941 W/m∙K.